2008
DOI: 10.1097/01.ncc.0000339250.83571.b0
|View full text |Cite
|
Sign up to set email alerts
|

Children's Experiences of Participation in a Family Support Program When Their Parent Has Incurable Cancer

Abstract: For a child, facing the imminent death of a parent is a highly stressful situation. This study assessed a preventive support program for children aged between 5 and 18 years and their families when a mother or father has an incurable form of cancer. We chose a family-based approach to reduce risk factors and enhance protective factors by increasing positive interactions between parents and children and by increasing their mutual understanding of the illness and its family impact. In this article, we focus espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
135
0
48

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(197 citation statements)
references
References 28 publications
14
135
0
48
Order By: Relevance
“…The reference lists of these articles were checked for any other relevant studies, resulting in one more study by Bugge, Helseth and Darbyshire. [25,26] Eleven studies published from 1995 to 2009, and conducted in the USA (n = 7); UK (n = 1); Australia (n = 1) and Norway (n = 2) were finally included in the current integrative review. Six of the studies used a qualitative approach, whereas the other five studies were based on quantitative methods.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reference lists of these articles were checked for any other relevant studies, resulting in one more study by Bugge, Helseth and Darbyshire. [25,26] Eleven studies published from 1995 to 2009, and conducted in the USA (n = 7); UK (n = 1); Australia (n = 1) and Norway (n = 2) were finally included in the current integrative review. Six of the studies used a qualitative approach, whereas the other five studies were based on quantitative methods.…”
Section: Resultsmentioning
confidence: 99%
“…[26] Children need to be in dialogue with other family members, but Bugge showed that the children also need support, without having to think about family members' reactions. [25] The data analysis and reduction from the review revealed a number of themes and subcategories across the included studies, as depicted in Table 3. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Semptomların tanılanması ve yönetiminde sağlık profesyonelleri kadar çocuk ve ebeveyne de önemli rol düşmekte, ancak çalışmalar ebeveynlerin bu süreci yönetmede yeterli olmadığını göstermektedir. Ayrıca ebeveynlerin, çocuklarında kanser tedavisinin yan etkilerine bağlı oluşan semptomları belirlemede ve uygun girişimler uygulamada zorlandıkları belirtilmektedir (13,32). Yaşam kalitesini olumsuz yönde etkileyen semptomlar arasında yer alan yorgunluğun tanılanması ve yönetimi çocuk ve ailesi açısından önem taşımaktadır (13,32).…”
Section: Yorgunluğun Yaşam Kalitesi üZerine Etkileriunclassified